Pengaruh Pelatihan dan Pengembangan terhadap Kinerja Karyawan dengan Motivasi sebagai Variabel Intervening: Studi Kasus di PT. Perkebunan Nusantara IV Regional 1 Kebun Gunung Monako - Nurlita Utari; Irfan; Suwadi; Willy Cahyadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to evaluate the influence of Training and Development on Employee Performance with Motivation as an intervening variable at PT. Perkebunan Nusantara IV Regional 1 Kebun Gunung Monako. The sample was selected using purposive sampling, with criteria being field employees who have participated in training and development programs, specifically harvesters, totaling 30 individuals. Primary data was collected through questionnaires using a Likert scale (1–5) to measure the variables of Training, Development, Motivation, and Employee Performance. Secondary data was obtained from the company's internal documentation. Data analysis was conducted using the Inner Model test in the Structural Equation Modeling (SEM) technique with the SMART PLS software to examine the relationships among latent variables in the structural model, aiming to test the relationships and measure the strength and significance of the existing paths. The data analysis in this research is quantitative. The results show that: Training does not affect Employee Performance; Training does not affect Motivation; Development does not affect Employee Performance; Development does not affect Motivation; Motivation does not significantly affect Employee Performance; Training does not affect Employee Performance through Motivation as an intervening variable; and Development does not affect Employee Performance through Motivation as an intervening.